Analisis Sosiodemografi dan Pola Nafkah Petani Penggarap di Tanah Eks Perkebunan Swasta Jawa Barat - Yayat Sukayat; Achmad Choibar Tridahusumah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
The long history of the South West Java region is also the history of large private plantations stretching from the colonial era to the current situation. Another reality shows that generations of plantation workers who lived for generations, trying to survive by utilizing the land of former private plantations. This study aims to determine the sociodemographic conditions farmers that cultivated ex-private plantations in Cianjur Regency and their livelihoods. The research method uses a survey and descriptive statistical analysis, while the sample is farmers who cultivated on ex- private plantation. The results showed that the farmers in the study area had an age range between 18 to 82 years. The age structure of smallholder farmers shows the productive age of both male and female smallholder farmers. The average family dependent is 3 people and most tenants own ≤ 0.5 hectares of land. The pattern of livelihood of the family of the tenants depends on the agriculture of paddy fields, utilization of forest products in the form of wood, construction workers and other jobs to fulfill the lives of the farmers and their family.